Path Analysis on the Effectiveness of Chronic Disease Prevention Program using Health Belief Model - Nafi’ah Aprilia; Didik Tamtomo; Endang Sutisna Sulaeman (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Chronic disease prevention program is a proactive health service system on chronic diseases which can affect hypertension control. This study aimed to determine the effect of the chronic disease prevention program and the construction of the Health Belief Model (HBM) on the prevention of elderly hypertension with path analysis method.Subjects dan Method: This study used observational analytical study with retrospective cohort study approach. This study was conducted in four community health centers in Ngawi Regency, East Java, in April-May 2019. The total sample of 200 elderly aged 60-74 years was divided into2 groups, such as group which participated in chronic disease prevention program(case) and the group which did not participate in chronic disease prevention program(control) based on fixed exposure sampling. The dependent variable of this study was hypertension control. The independent variables in this study were participants in a chronic disease prevention program, perceived vulnerability, perceived seriousness, perceived benefits, perceived barriers, cues to action, and self-efficacy. Variable data collection used questionnaires and analyzed using path analysis.Results: Hypertension control was directly and positively affected by chronic disease prevention program(b= 2.85; 95%CI= 0.48 to 5.22; p= 0.018), perceived vulnerability (b= 1.35; 95%CI= 0.16 hingga 2.53; p= 0.025), perceived seriousness (b= 0.83; 95%CI= 0.04 to 1.62; p= 0.039), and self-efficacy (b= 0.99; 95%CI= 0.14 to 1.85; p= 0.023). Hypertension control was indirectly affected by perceived benefits, perceived barriers, and cues to action.Conclusion: Hypertension control in the elderly is directly and positively affected by participation in chronic disease prevention program, perceived vulnerability, perceived seriousness, and self-efficacy. Hypertension control is indirectly affected by perceived benefits, perceived barriers, and cues to action.Keywords: Hypertension, chronic disease, prevention, Health Belief Model, path analysisCorrespondence: Nafi’ah Aprilia. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: nafiahlia@gmail.com. Mobile: 082230766393Journal of Health Promotion and Behavior (2019), 4(2): 85-97https://doi.org/10.26911/thejhpb.2019.04.02.01